The complete mitochondrial genome of Agelasta perplexa Pascoe (Coleoptera: Cerambycidae) - Yanting Li; Runkai Chen; Hanzhu Jia; Xuemin Lei; Jiayi Ma; Songqing Wu (Mitochondrial DNA. Part B. Resources, 2021)
Agelasta perplexa Pascoe is a mulberry borer that threatens the health of the plant. This study revealed the length of the complete mitochondrial genome of A. perplexa which consists of 15,552 bp length with 39.8% A, 12.8% C, 8.4% G, and 39.1% T, respectively. The GC content of whole mitochondrial genome is 21.1%. The complete mitochondrial genome encodes 12 protein-coding genes (PCGs), 22 tRNAs, two rRNAs, and one AT-rich region. This study can facilitate further research about genetic evolution as well as prevention and control strategy of A. perplexa.